Supplementation of L-arginine in pregnant gilts affects the protein abundance of DNMT1 in 35-day fetuses - Costa, Karine Assis [UNESP]; Barbosa, Lívia Maria dos Reis; Marques, Daniele Botelho Diniz; da Silva, Walmir; Camilo, Breno Soares; de Souza Netto, Domingos Lollobrigida; Saraiva, Alysson; Guimarães, José Domingos; Guimarães, Simone Eliza Facioni (Elsevier, 2024)
Maternal nutrition is one of the main environmental factors regulating gene expression during fetal development through epigenetic modifications. Some nutrients, such as the amino acid L-arginine, are added to maternal diets to modulate gene expression, improve the reproductive performance of females, and enhance conceptus development. This study investigated the hypothesis that supplementation of pregnant gilts with L-arginine regulates gene expression in conceptuses through epigenetic mechanisms. For this, fetal programming phenotypic markers, the expression of key epigenetic genes, and the abundance of DNA methylation proteins (DNMT3A and DNMT1) were evaluated in 25- and 35-day conceptuses from gilts supplemented (ARG) or not (CON) with 1.0 % L-arginine during early gestation. At 25 days, there were no significant differences in phenotypic markers between CON and ARG embryos (P > 0.05). Similarly, no differences were found between CON and ARG fetuses at 35 days (P > 0.05). Maternal supplementation with L-arginine did not influence the expression of the evaluated key epigenetic genes in pig embryos or fetuses, nor DNMT3A protein abundance (P > 0.05); on the other hand, DNMT1 protein abundance was lower in ARG fetuses (P = 0.002). It is concluded that supplementation of L-arginine in pregnant gilts affects epigenetic mechanisms, such as DNA methylation, in 35-day fetuses through regulation of DNMT1 levels. Further studies using transcriptomic and proteomic analysis could reveal additional epigenetic modifications in embryos and fetuses following maternal supplementation with L-arginine.
Keywords: Development; DNA methylation; Fetal programming; Nutrigenomics; Post-translational histone modifications